FUNGSI INPUT’S DALAM PENYUSUNAN RENCANA STRATEGIS (STUDI DI DIREKTORAT JENDERAL PLANOLOGI KEHUTANAN DAN TATA LINGKUNGAN) - Putri Indahsari (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This paper is a study to find out about the inputs used in the strategic plan process and to offer an alternative to the input's need for strategic plan arrangement in the next period precisely. The research was conducted by using qualitative method with descriptive approach. The research results show that the 2015-2019 Strategic Plan arrangement process used mix approach between top down and bottom up approach. The evaluation’s results of the previous 2010-2014 Strategic Plan were used as the basis/inputs in preparing the 2015-2019 Strategic Plan. Moreover, the availability of resources, future goals and challenges, and the Strategic Plan of the Ministry of Environment and Forestry also were used as the inputs for arranging 2015-2019 Strategic Plan.